Reconceptualizing Educational Human Resources Development: A Systematic Literature Review of Concepts, Practices, and Leadership Roles - Liah Siti Syarifah; Asep Suryana; Aip Syaepul Uyun; Johar Permana (Institut KH Ahmad Sanusi (INKHAS) Sukabumi, 2026)
This article examines the mapping and reconceptualization of Human Resource Development (HRD) within educational institutions through a Systematic Literature Review (SLR) combined with bibliometric analysis. The study is grounded in the need to contextualize HRD in the education sector, as most HRD literature remains dominated by corporate perspectives. The research focuses on the concepts, components, practices, and leadership roles involved in educational human resource development. The SLR process followed the PRISMA protocol, including identification, screening, eligibility assessment, and inclusion, with data drawn from Scopus, Crossref, and Google Scholar. Thematic analysis was applied to synthesize conceptual findings, while bibliometric analysis using VOSviewer mapped the intellectual structure and dominant clusters within the HRD discourse. The results indicate that HRD in educational settings is strategic and long-term in orientation, encompassing human capital planning, talent development, performance management, reward systems, HR digitalization through HRIS, and organizational development. Bibliometric findings also highlight the central role of human capital and leadership as key drivers of HRD effectiveness. The main conclusion emphasizes the need to reconceptualize HRD not merely as an effort to enhance individual competencies but as an institutional transformation tool that strengthens organizational capacity and fosters a sustainable learning culture. Thus, HRD emerges as an essential institutional strategy for ensuring the long-term quality and sustainability of educational institutions.